Neonatal retropharyngeal abscess with complications: Apnea and cervical osteomyelitis. (November 2019) - Ali, Noor-E-Seher; Alyono, Jennifer C.; Koltai, Peter J.
Abstract: Objective: To evaluate the clinical presentation and management strategies for neonatal retropharyngeal abscess (RPA). Methods: Retrospective chart review was performed, and literature reviewed. Results: We report two cases of neonatal RPA, with one complicated by cervical osteomyelitis, and the other presenting with apparent life-threatening events (ALTEs). A 6-week-old female underwent transoral drainage of an RPA, which grew methicillin sensitive Staphylococcus aureus . She had a prolonged recovery course and was found to have developed osteomyelitis of the dens and atlas. She was treated with 14 weeks of IV antibiotics and rigid collar fixation for spinal cord instability. A 2-month-old female was admitted after multiple ALTEs with episodes of apnea and pallor. Direct laryngoscopy revealed a bulging RPA, which was drained transorally. This grew multiple organisms including methicillin resistant Staphylococcus aureus, Streptococcal oralis and Prevotella species. Conclusions: Uncommon in neonates, RPA can present in this age group without fever, and are is likely to have airway complications than in older children. In cases with prolonged recovery, additional diagnostic intervention is recommended to rule out rare complications such as osteomyelitis. Emphasis in such complex cases is placed on a multidisciplinary approach to patient care, coordinating neonatologists, infectious disease specialists, neurosurgeons, and otolaryngologists.